Model for Utilizing Corporate Social Responsibility in Improving the Welfare of the Community of Industrial Area in West Java - Sitti Faoziyah (GoAcademica Research & Publishing, 2023)
The purpose of this study was to analyze the role of corporate social responsibilty (CSR) in improving people's welfare. The approach used in this research is a combination of quantitative and qualitative. The research location is PT. Pertamina (Persero) RU VI in Balongan Indramayu, West Java. Data collection techniques were carried out by survey methods, participatory observations, and in-depth interviews. The survey method was carried out by distributing questionnaires to the corporate social responsibilty (CSR) recipient communities, and observation and interviews were conducted to find out the experiences, understandings, and in-depth meanings of the participants' actions. The focus of the research topic is corporate social responsibilty (CSR) and community welfare. The findings reveal two main topics. First, quantitatively corporate social responsibilty (CSR) has a very large influence on improving the welfare of the community receiving CSR funds, so it is necessary to increase the increase in corporate social responsibilty (CSR) provided to the community, as well as the need to expand the scope of the location of the recipient community. Second, qualitatively, corporate social responsibilty (CSR) which is currently being implemented has a positive impact on people's welfare. However, it is necessary to improve other principles of business ethics, namely the principles of honesty, fairness, autonomy in order to create effective business ethics in a common framework. The government needs to support and provide strict supervision of the implementation of corporate social responsibilty (CSR) programs in order to be able to have a positive impact on improving people's welfare.